Правові, організаційні й тактичні аспекти доказової діяльності захисника в кримінальному провадженні - Павліченко, Є. В.; Анненко, О. С.; Annenko, O. S.; Pavlichenko, Ye. V. (Одеса : Гельветика, 2021)
У статті визначаються правові, організаційні й практичні аспекти діяльності захисника в кримінальному провадженні. На основі аналізу роботи органів досудового розслідування виявлені проблеми, які потребують правового врегулювання з визначенням повноважень суб’єктів сторони обвинувачення та захисту й внесення змін і доповнень до чинного кримінально процесуального законодавства. У статті визначено поняття, сутність процесуального статусу захисника в кримінальному процесі; надана характеристика участі захисника на стадії досудового розслідування; висвітлено інститут самостійного адвокатського розслідування в кримінальному провадженні; розкрито участь захисника на стадії судового розгляду; обґрунтовано доказову діяльність захисника; визначено шляхи вдосконалення правової регламентації участі захисника в кримінальному провадженні. На основі проведених досліджень було запропоновано внести зміни й доповнення, які, з одного боку, визначать чітко функцію та роль слідчого судді в кримінальному провадженні, а з іншого, – підвищать гарантії його процесуальної самостійності. Доведено, що дотриманню прав і свобод громадян сприятиме процесуальна діяльність керівника органу досудового розслідування, яка покликана забезпечити умови для ефективної роботи підлеглих і контроль за дотриманням ними вимог законодавства. У статті звернено увагу на те, що серед суб’єктів, які на підставі отриманих фактичних даних встановлюють наявність чи відсутність фактів та обставин, котрі мають значення для кримінального провадження та підлягають доказуванню, захисника не визначено. Установлено, що між певними положеннями кримінального процесуального кодексу України існує правова протилежність. Показано, що захисник має право збирати відомості про факти, що можуть бути використані як докази. Доведено, що захисник має право отримувати докази в кримінальному провадженні шляхом ініціювання проведення слідчих дій, негласних слідчих (розшукових) дій та інших процесуальних дій у випадках, передбачених Кодексом. Показано, що ініціювання захисником проведення слідчих дій, негласних слідчих дій та інших процесуальних дій повинно здійснюватися шляхом подання слідчому або слідчому судді відповідних клопотань. Доведено, що тактика захисника – це спосіб його практичної діяльності, який являє собою сукупність тактичних прийомів, вироблених криміналістичною наукою, котрі використовуються ним для здійснення тактичного впливу на психіку об’єкта такого впливу, спрямованого на подолання протидії, що чиниться цим об’єктом, або на спонукання цього об’єкту до вчинення певних дій в інтересах захисту (за відсутності явної протидії) з метою досягнення захисником поставленої мети для реалізації функції захисту. Щодо тактики сторони захисту в цілому, то це питання дискусійне й потребує додаткового дослідження. У статті надана аргументація необхідності наділення захисника правом самостійного проведення процесуальних дій, у межах яких існувала б можливість комплексного застосування пізнавальних і посвідчувальних операцій залежно від характеру слідів розслідуваної події.

The article presents ideas on the general structure of the methodology of professional protection in criminal proceedings, which main elements include: forensic characteristics of the relevant type of criminal offense; determination of priority general tactical tasks of defence at the stage of entry of a defence lawyer into the process; selection of a typical position of protection in view of the current situation and practice of professional protection in the relevant criminal proceedings; establishing the circumstances, which proof will help to obtain the most favourable final decision for the client; tactical features of the performance of a defence lawyer during the criminal proceedings on a premeditated murder. Analysis of the provisions of criminal procedure law, which determine the means of gathering evidence by the defence, showed that the defence lawyer is essentially deprived of the possibility of independent procedural actions, where there would be a possibility of comprehensive cognitive and identification operations depending on the nature of the investigation. However, the tasks of the investigation of a lawyer cannot be fully realized without such actions. It is emphasized that there can be no special procedure for collection of evidence by a defence lawyer within a lawyer’s investigation, which would be significantly different from similar actions of an investigator or a prosecutor during pre-trial investigation. Otherwise, there will always be a possibility of discriminatory treatment of the evidentiary value of the results of the lawyer’s investigation. Procedural differences in the conduct of procedural actions to collect evidence by the investigator (prosecutor) and those of a defence lawyer may be due to only one factor – the lack of power to use coercion or any other restriction of human and civil rights and freedoms by the latter. The article defines the legal, organizational and practical aspects of the defender’s activity in criminal proceedings. Based on the analysis of the work of the pre-trial investigation bodies, the issues have been identified that require legal settlement with the definition of the powers of the prosecution and defence and the introduction of changes and additions to the current criminal procedure legislation. The article defines the concept, the essence of the procedural status of a defender in criminal proceedings; the characteristic of participation of a defender at the stage of pre-judicial investigation is given; the institute of independent lawyer’s investigation in criminal proceedings is covered; the participation of a defence lawyer at the stage of trial is revealed; the evidentiary activity of a defence lawyer is substantiated; the ways to improve the legal regulation of the participation of a defence lawyer in criminal proceedings are identified. Based on the research, it was proposed to make changes and additions that, on the one hand, will clearly define the function and role of the investigating judge in criminal proceedings, and on the other hand, increase the guarantees of his procedural independence. It is proved that observance of the rights and freedoms of citizens will be facilitated by the procedural activity of head of the pre-trial investigation body, which is designed to provide conditions for effective work of subordinates and control their compliance with the law. The article draws attention to the fact that among the subjects who, on the basis of the obtained factual data, establish the presence or absence of facts and circumstances relevant to the criminal proceedings and subject to proof, there is no defence lawyer. It is established that there is a legal contradiction between certain provisions of the CPC of Ukraine. It is shown that a defence lawyer has the right to gather information about facts that can be used as evidence. It has been proved that a defence lawyer has the right to obtain evidence in criminal proceedings by initiating investigative actions, covert investigative (search) actions and other procedural actions, in cases provided for by this Code. It is shown that the initiation of investigative actions by the defence lawyer, covert investigative actions and other procedural actions should be carried out by submitting appropriate motions to the investigating judge. It is proved that the tactics of the defender is a way of his practical activity, which is a set of tactics developed by forensic science, which he uses to exercise tactical influence on the object of such influence, aimed at overcoming the resistance of this object, or to encourage this object to take certain actions in the interests of protection (in the absence of explicit opposition), in order to achieve the goal set by the defender to implement the function of protection. Regarding the tactics of the defence in general, this issue is debatable and needs further study. The article provides an argument for the necessity to give the defender the right to conduct procedural actions independently, where there would be a possibility of comprehensive application of cognitive and identification operations, depending on the nature of the traces of the investigated event.
Павліченко Є. В. Правові, організаційні й тактичні аспекти доказової діяльності захисника в кримінальному провадженні / Є. В. Павліченко, О. С. Анненко // Актуальні проблеми держави і права : зб. наук. пр. Вип. 91 / редкол.: Г. I. Чанишева (голов. ред.) та ін. – Одеса : Гельветика, 2021. – С. 142-149.
Keywords: гарантії; слідчі дії; законність; обґрунтованість; негласні слідчі дії; суб’єкти забезпечення захисту прав; тактика захисника; Research Subject Categories::LAW/JURISPRUDENCE; guarantees; investigative actions; legality; validity; covert investigative actions; subjects of protection of rights; tactics of the defender